POLITIK LEGALISASI: SIKAP SINGAPURA, MYANMAR, DAN INDONESIA DALAM PENYUSUNAN PIAGAM ASEAN - , Prima Agung Saputra ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The presence of ASEAN Charter induce many reactions. There are people who appreciate and people who criticize the charter. People who appreciate it said that the establishment of ASEAN Charter was a milestone. With the charter, ASEAN is no longer a soft-regulated association but also a legally- constituted institution. Meanwhile, people who criticize it argue that establishing ASEAN Charter will not give important change for ASEAN because the provisions regulated on ASEAN Charter are not new. This research examined the legalization form of ASEAN Charter, whether the regulation is soft or hard. Then, the research analized the position of Singapore, Myanmar, and Indonesia during the drafting process of ASEAN Charter. According to the Politics of International Law and by using liberalism perspective, the legalization form of ASEAN Charter is soft law to moderate. ASEAN Charter was established with the form above because of disparity in each member state, at their political security, economic, and socio cultural conditions. In addition, each member states had national interest in the establishment of the charter. Although the drafting process of ASEAN Charter was really difficult and spent much of time, the ASEAN Charter was successfully established. It showed the importance of ASEAN Charter as a legal framework for ASEAN. In broad perspective, the establishment of ASEAN Charter showed the importance of international law as an instrument of cooperation for international actors.